Optimization of a pisciponic system using lemon fin barb hybrid and selected herbs - Oriohekaino, Ogah Samuel Ijabo (2019)
In conventional aquaculture systems, only about 25% of the dietary N input is recovered by fish. In a pisciponic system in which fish and vegetables are cocultured in a balanced ecosystem, vegetables recover the nutrients from the fish wastes. The general objective of this research was to study the viability of coculturing hybrid lemon fin barb and culinary herbs in a pisciponic system. Experiment 1 was conducted to determine the optimal stocking density of hybrid lemon fin barb in a recirculating aquaculture system (RAS). Fish were stocked at 25, 50, 75 and 100 fish tonne-1 and were monitored for welfare and growth in terms of weight gain, feed conversion and survival. This experiment was carried out in 12 weeks. The quality of the culture medium was judged using basic water quality parameters and found to be optimal. The highest fish growth was recorded at a stocking rate of 25 fish tonne-1. In Experiment 2, the hybrid lemon fin barb was stocked at 25 fish tonne-1 in 12 identical pisciponic units. Three common Malaysian culinary herbs, Chinese celery, coriander and peppermint, were grown using the nutrient film technique (NFT) and the waste water from the fish tanks. Water quality tests such as nitrogen, phosphorus, potassium, total dissolved solids, pH, dissolved oxygen, conductivity and temperature were monitored through a 7-week study. The growth, production and NPK composition of fish and herbs were measured. The nutrient retention by the fish and herbs were also estimated. The results showed that the survival of fish was not affected by the different herbs however, the fish co-cultured with peppermint had significantly higher weight gain compared to those cultured with Chinese celery and coriander. However, the growth and production of peppermint were significantly higher than those of Chinese celery and coriander. The fish was consistent in nutrient recovery of 32% N, 36% P and 36% K. The NPK recovery for peppermint were 31%, 5% and 7% while NPK recovery for Chinese celery and coriander were 21% N, 3% P and 4% K each. The total NPK recovery for the system was 47-56% for N, 39-42% for P and 37-45% for K. At the end of this experiment, 44-53% N, 58-61%P and 55-63% K were retained by the wastewater. The effects of night lighting using LED red and blue plant grow-lights on production of herbs were studied in Experiment 3. In this study, peppermint was used in order to further enhance its production. The plants were subjected to a 12 h ambient daylight and 0, 6 and 12 h night lighting respectively for a period of 14 weeks (two batches of 7 weeks each). Peppermint responded positively to increased night-lighting hour. A significant faster growth was observed based on stem length, leaf numbers and production mass (19% higher with 12 h night-lighting) at harvest. Approximately 18% more nutrients were taken up with night lighting. The total recovery of the hybrid lemon fin barb-peppermint system with a 12-h natural day lighting and 12-h night lighting ranged from 27-34% for N, 41-49% for P and 25-31% for K. In conclusion, the hybrid lemon fin barb was proven a good potential candidate for a pisciponic system. Its waste was successfully utilized by tested culinary herbs especially peppermint. The total system recovery was 21-65% N, 36.9-47% P and 23-43% K. These findings showed that more than double of peppermint pots could be incorporated into the system for higher nutrient recovery.